The Malolotsha Klippe: Large‐Scale Subhorizontal Tectonics Along the Southern Margin of the Archean Barberton Greenstone Belt, Eswatini. Issue 1 (3rd January 2023) - Heubeck, Christoph; Thomsen, Tonny B.; Heredia, Benjamin D.; Zeh, Armin; Balling, Philipp
Abstract: Whether Archean tectonics were horizontally or vertically dominated is controversially discussed because arguments bear on the kinematics and thermal state of the Archean mantle and constrain the mode of formation of the earliest continental crust. Highly deformed strata of Archean greenstone belts figure prominently in this debate because they record long periods of time and multiple deformation phases. Among the best‐preserved greenstone belts counts the Barberton Greenstone Belt (BGB) of southern Africa. Geological mapping of part of the southern BGB in Eswatini (Swaziland), combined with U‐Pb zircon dating, shows that the region preserves a tightly re‐folded imbricate thrust stack in which metavolcanic and ‐volcaniclastic strata of the Onverwacht Group, deposited at 3.34–3.29 Ga, have been thrust on top of ca. 3.22 Ga siliciclastic strata of the Moodies Group. The structurally highest element, the Malolotsha Syncline, forms a tectonic klippe of substantial size and is >1, 450 m thick. Forward modeling of a balanced cross section indicates that this thrust stack was part of a northwestward‐verging orogen along the southern margin of the BGB and records a minimum horizontal displacement of 33 km perpendicular to its present‐day faulted, ductily strained and multiply metamorphosed margin. Because conglomerate clasts indicate a significantly higher degree of prolate strain which extends further into the BGB than at its northern margin, late‐stage tectonic architecture of the BGB may be highly asymmetrical. Our study documents that the BGB, and perhaps other Archean greenstone belts, preserves a complex array of both vertically‐ and horizontally‐dominated deformation styles that have interfered with each other at small regional and short temporal scales. Plain Language Summary: Worldwide, only a few regions exist where ancient rock strata document how earth cooled, surface strata deformed, and continents grew. It is debated whether vertical movements dominated (akin to a lava lamp) and when major horizontal motions (as they dominate Earth today) began; certainly, there was also overlap between these regimes. Radiometric age dating of zircons extracted from strata along the southern margin of one of the best‐preserved ancient regions in southern Africa, the Barberton Greenstone Belt in Eswatini, show that older strata were thrust there over younger strata for at least 33 km distance subhorizontally. Then they were shingled, and then folded. The results show that even at a time when Earth's oldest continents were just forming, significant horizontal displacements existed already. Key Points: U‐Pb zircon dating and geological mapping confirm a folded thrust‐stack along part of the southern margin of the Archean Barberton Greenstone Belt (BGB) Forward modeling of a balanced cross‐section indicates >33 km of horizontal shortening toward the northwest Vertically‐ and horizontally‐dominated tectonics interfered with each other in the BGB and may have done so in other Archean greenstone belts as well